Reforma Agraria di Perkotaan, Usaha Mencari Bentuk: Kasus Jakarta, Indonesia - Muh Kamim, Anggalih Bayu (Jurnal Aspirasi, 2022)
This research explores the effort of residents in Jakarta to defend their land and housing rights. The research question is: How are the residents’ efforts to carry out land reform by leverage in Jakarta? This study uses a case study method with data collected from government documents, journal articles, online media, and other types of secondary data. Data collecting is also done through in-depth interviews and focus group discussions with civil society activists, residents of Kampung Kota, and the administrator of Jakarta’s Agrarian Reform Task Force. Data analysis is carried out through the planning process, reviewing the literature, collecting data, to presenting and drawing a conclusion. The results of the study indicate that three foundations encourage the emergence of agrarian reform under which the residents have carried out namely the long experience of policy advocacy, the use of community action plans, and the emergence of the Agrarian Reform Task Force. Recognition through social mapping to the preparation of participatory village flat designs is an essential instrument for villagers to fight for their rights. Residents together with their social networks succeeded in encouraging 21 villages as objects of agrarian reform in Jakarta. The solidarity of the movement, support from civil society networks, and successful negotiations with Anies Baswedan became the entry point for agrarian reform from below in Jakarta. Civil society networks still have problems that must be resolved together with other stakeholders to formulate the correct form of urban agrarian reform and solve the problem of agrarian sectoral nationally.AbstrakKajian ini mendalami upaya warga kampung di Jakarta dalam memperjuangkan hak atas tanah dan hunian. Pertanyaan penelitiannya adalah bagaimana upaya warga kampung kota melakukan reforma agraria dari bawah di Jakarta? Studi ini menggunakan metode studi kasus melalui proses penelusuran atas dokumen pemerintahan, artikel jurnal, media daring, dan sumber sekunder lainnya. Pengumpulan data juga dilakukan melalui wawancara mendalam dan focus group discussion bersama para pegiat masyarakat sipil, warga kampung, dan pengurus Gugus Tugas Reforma Agraria (GTRA) Jakarta. Analisis data dilakukan melalui proses perencanaan, penyusunan kajian literatur, pengumpulan data, sampai dengan penyajian dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa ada tiga landasan yang mendorong munculnya reforma agraria dari bawah yang dilakukan oleh warga yakni pengalaman panjang advokasi kebijakan, pemanfaatan community action plan, dan munculnya GTRA. Rekognisi melalui pemetaan sosial sampai dengan penyusunan desain kampung susun secara partisipatif menjadi instrumen penting bagi warga kampung untuk memperjuangkan hak-haknya. Warga bersama jejaring sosialnya berhasil mendorong 21 kampung sebagai objek reforma agraria di Jakarta. Soliditas gerakan, dukungan dari jejaring masyarakat sipil, dan keberhasilan negosiasi dengan Anies Baswedan menjadi pintu masuk bagi reforma agraria dari bawah di Jakarta. Jejaring masyarakat sipil masih memiliki masalah yang harus diselesaikan bersama dengan pemangku kepentingan lainnya untuk merumuskan bentuk reforma agraria perkotaan yang tepat dan menyelesaikan problem sektoral agraria secara nasional.